Efficacy and safety of early radiotherapy combined with first-line chemo-immunotherapy in extensive-stage small-cell lung cancer: a multi-center analysis - Jia, Jingyi; Zeng, Ya; Ji, Yongling; Zhu, Hui; Meng, Rui; Xia, Bing; Wang, Yunfeng; Shen, Tianle; Su, Xi; Zhou, Tongfang; Lu, Yifei; Zhao, Lei; et al. (Frontiers in Immunology, 2026)
BackgroundsThis study aimed to evaluate efficacy and safety of early radiotherapy combined with first-line chemo-immunotherapy in patients with extensive-stage small-cell lung cancer (ES-SCLC).MethodsES-SCLC patients treated with first-line chemo-immunotherapy from August 2018 to January 2024 at five centers were included. Patients receiving early radiotherapy administered before disease progression were categorized into RT group, and were further separately stratified by the receipt of thoracic radiotherapy (TRT) and extra thoracic radiotherapy (eTRT). Propensity score matching (PSM) was performed to balance potential bias.ResultsTotally, 771 patients were enrolled. RT group exhibited significantly better progression-free survival (PFS, p<0.001) and overall survival (OS, p<0.001) compared to Non-RT group in the whole and post-PSM cohort. The survival benefit was also observed in TRT group versus Non-TRT group, and eTRT group versus Non-eTRT group. Exploratory analyses were conducted within the TRT group. Consolidative TRT was associated with superior PFS (p<0.001) and OS (p=0.006) compared to the concurrent treatment. Additionally, survival outcomes were comparable between patients receiving a biological effective dose (BED) below or above the median dose of 60Gy and the salvage dose of 39Gy. No significance was observed in overall adverse events between RT group and Non-RT group, despite a higher rate of all-grade pneumonitis in RT group (9.9% versus 4.2%, p=0.002).ConclusionsEarly radiotherapy, either thoracic or extra thoracic radiotherapy, combined with first-line chemo-immunotherapy constituted an effective and well-tolerated strategy for patients with ES-SCLC. These findings warrant investigation in prospective randomized trials.